New Current-Mode Notch and Allpass Filters with Single Current Difference Amplifier - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
A new configuration for realization of current-mode notch and allpass filters is presented. It can synthesize second-order notch and allpass filters using a single current difference (Norton) amplifier and at most eight passive RC one port elements. Experimental results obtained from a notch filter realization are presented.